2004
DOI: 10.1002/ijc.20370
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms and haplotype structures in genes for transforming growth factor β1 and its receptors in familial and unselected breast cancers

Abstract: Alterations in TGF-␤ signaling appear to be associated with an altered risk of developing cancer, including breast cancer. We carried out a case-control study on 8 polymorphisms, including 5 in the TGF-␤1 gene (G-800A, C-509T, Leu 10 3 Pro, Arg 25 3 Pro and Thr 263 3 Ile), a polyalanine polymorphism (9A36A) in the TGF-␤RI gene and 2 (G-875A and A-364G) in the TGF-␤RII gene, using samples from 2 different populations, Polish familial and Finnish unselected breast cancer cases, together with ethnically and geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
78
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 31 publications
6
78
2
Order By: Relevance
“…Additionally, previous studies indicated that the TGFBR2 G-875A variant was not associated with breast cancer risk in the European population (21). However, results of the present study have shown that the -875A allele was marginally associated with a decreased risk of breast cancer.…”
Section: Discussioncontrasting
confidence: 78%
“…Additionally, previous studies indicated that the TGFBR2 G-875A variant was not associated with breast cancer risk in the European population (21). However, results of the present study have shown that the -875A allele was marginally associated with a decreased risk of breast cancer.…”
Section: Discussioncontrasting
confidence: 78%
“…Several genetic polymorphisms exist in the TGF-b1 gene, one of which is a T-C transition at nucleotide 29 of the coding region, resulting in a leucine to proline substitution at codon 10 (Blobe et al, 2000;Breast Cancer Association Consortium, 2006;Cox et al, 2007). This single nucleotide polymorphism (SNP) T29C, which is in strong linkage disequilibrium with another common SNP C-509T, has been studied extensively for its association with breast cancer risk and survival (Yokota et al, 2000;Goode et al, 2002;Hishida et al, 2003;Krippl et al, 2003;Ziv et al, 2003;Jin et al, 2004;Le Marchand et al, 2004;Shu et al, 2004;Kaklamani et al, 2005;Lee et al, 2005;Shin et al, 2005;Skerrett et al, 2005;Breast Cancer Association Consortium, 2006;Feigelson et al, 2006;Gonzalez-Zuloeta Ladd et al, 2007). Two studies found increased risk of breast cancer among Koreans and Dutch who carry the C allele (Lee et al, 2005;Gonzalez-Zuloeta Ladd et al, 2007), whereas two other studies showed decreased risk in relation to C genotype among Americans who were older than 65 years or Japanese who were premenopausal (Hishida et al, 2003;Ziv et al, 2003).…”
mentioning
confidence: 99%
“…12 This promoter variant may alter TGFB1 transcription activity and the binding of the transcription factor Yin Yang 1. 18 Due to its functional relevance, several molecular epidemiological studies were performed to investigate the relationship between TGFB1 polymorphisms and risk of cancers, including breast-, 15,[19][20][21][22][23][24][25][26] prostate- 27,28 and hepatocellularcarcinoma. 16,17 However, to date no studies have focused on gastric cancer in Chinese population.…”
mentioning
confidence: 99%